Purr-suasion in Action: How Catvertising BoostsBrand Recall through Cognitive Fluency - Achmad Ridha; Hasisa Haruna; Fina Ruzika Zaimar; Wiwin Riski Windarsari; Adriansyah (Candela Edutech Indonesia, 2025)
The Objectives – This study investigates how catvertising, or the strategic use of cat imagery in social-media advertising, influences brand recall through the mediating role of cognitive fluency. The research aims to understand how emotional engagement and cognitive simplicity jointly enhance advertising effectiveness in digital environments. The Methods/approaches – Using a quantitative, cross-sectional approach, data were collected from 100 active social-media users aged 18–35 in Makassar City, Indonesia. Respondents were exposed to simulated social-media advertisements containing or excluding cat imagery and subsequently completed a seven-point Likert-scale questionnaire measuring catvertising, cognitive fluency, and brand recall. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, consisting of two stages: outer-model and inner-model evaluation. The Results – The results reveal that catvertising has a significant positive effect on brand recall, while cognitive fluency also enhances recall independently. However, the interaction effect between catvertising and cognitive fluency is not significant, indicating that emotional appeal and processing ease operate as parallel rather than moderating mechanisms. The Research Implications – These findings contribute to the theoretical integration of affective and cognitive perspectives in digital advertising research and highlight the importance of emotionally resonant yet cognitively simple designs. For practitioners, the study emphasizes the managerial relevance of incorporating familiar and emotionally appealing visuals to strengthen brand memorability in competitive social-media contexts.